Analysis of Thermochemistry Concept Understanding of Grade XI Students Based on the Consistency of Students’ Answers Using the Parallel Three-Tier Diagnostic Test - Friskawati Arkani; Mangara Sihaloho; Nita Suleman; Lukman Abdul Rauf Laliyo; Netty Ino Ischak (Universitas Negeri Gorontalo, 2026)
Thermochemistry is frequently regarded as difficult because students must connect observable heat phenomena, particle-level energy changes, and symbolic enthalpy calculations. This study aimed to analyze students’ thermochemistry concept understanding based on the consistency of their answers using a parallel three-tier diagnostic test. The research used a descriptive qualitative approach at SMA Negeri 1 Kabila during the odd semester of the 2025/2026 academic year. The subjects were 135 grade XI students. The instrument consisted of 20 parallel three-tier multiple-choice items arranged in 10 pairs that measured the same concepts through answer choices, reasoning choices, and confidence levels. Instrument quality was examined through expert validation and empirical testing using the Rasch model. The data were analyzed by calculating answer consistency and classifying students into knowing concept, misconception 1, misconception 2, misconception 3, and not understanding concept categories. The results showed that the average consistency of students’ concept understanding was only 29.48%, whereas inconsistency reached 70.52%. The average knowing concept category was 51.19%, followed by misconception 1 at 11.19%, misconception 2 at 16.84%, misconception 3 at 10.04%, and not understanding concept at 10.85%. These findings indicate that students’ thermochemistry understanding was not yet stable, especially for Hess law, calorimetry, and bond energy concepts.